‘It's a sanity restorer’: Narcotics anonymous (NA) as recovery capital during COVID-19 in Aotearoa New Zealand - Mappledoram M; Blake D; McGuigan K; Hodgetts D (John Wiley and Sons Ltd, 2024)
Narcotics Anonymous has flourished globally across 143 countries as a key community response to problematic substance use, despite disruptions, including the COVID-19 pandemic. This research sought to understand how the Aotearoa New Zealand Narcotics Anonymous (NA) community engaged with NA meetings online during the 2020–2021 COVID-19 pandemic. During in-depth, semi-structured interviews, 11 NA members shared their stories of addiction, abstinence-based recovery, experiences of NA and managing pandemic restrictions. A narrative analysis identified four tropes particularly relating to how community members managed during the pandemic: responding via technology; maintaining recovery connections; creating opportunities; and consistency. Each trope showcases how NA members were able to connect online and garner support for their abstinence-based recoveries and, more generally, during unprecedented times. In addition, the NA members in this research narrated the opportunities the pandemic restrictions created for them, such as engaging with the NA programme in new ways and improving their quality of life. Members of NA were able to maintain their psychological, physical, spiritual and community wellbeing during the COVID-19 pandemic primarily due to existing recovery capital—peer-based support and the principles of the 12-steps of NA. The implications are that access to peer-based communities and salient recovery identities are pivotal during ordinary and extraordinary times. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement.
Keywords: COVID-19; narcotics annoymous; peer support; recovery capital; substance use